Evaluation of muscle oxidative potential by 31P-MRS during incremental exercise in old and young humans - CHILIBECK, P. D; MCCREARY, C. R; MARSH, G. D; PATERSON, D. H; NOBLE, E. G; TAYLOR, A. W; THOMPSON, R. T (European journal of applied physiology and occupational physiology, 1998)
The purpose of this study was to compare muscle oxidative capacity between moderately active young and old humans by measuring intracellular threshold (IT) during exercise with 31P-magnetic resonance spectroscopy (31P-MRS). Changes in phosphocreatine, inorganic phosphate, and intracellular pH were measured by 31P-MRS during a progressive unilateral ankle plantar flexion exercise protocol in groups of moderately active old (n = 12, mean age 66.7 years) and young (n = 13, mean age 26.2 years) individuals. From muscle biopsy samples of the lateral gastrocnemius, citrate synthase (CS) activity was determined in six subjects from each group, and fibre type composition was determined in nine old and ten young subjects. The old group had a lower IT for pH, as a percentage of peak work rate (P < 0.05), despite a similar CS activity compared to the young. IT was significantly correlated with CS activity (R = 0.59; P < 0.05), but not with fibre type composition. It was concluded that metabolic responses to exercise are affected by ageing, as indicated by a lower IT in old compared to young individuals.